Identification of Phenolic Compounds and Evaluation of Antioxidant and Antimicrobial Properties of Euphorbia Tirucalli L. - de Araújo, Keline Medeiros (Antioxidants (Basel), 2014)
Bioactive compounds extracted from natural sources can benefit human health. The aim of this work was to determine total phenolic content and antioxidant activity in extracts of Euphorbia tirucalli L. followed by identification and quantification of the phenolic compounds, as well as their antibacterial activities. Antioxidant activities were determined by DPPH and ABTS(•+) assay. Identification of phenolic compounds was performed using high-performance liquid chromatography (HPLC), and antimicrobial activities were verified by agar dilution methods and MIC values. Total phenolic content ranged from 7.73 to 30.54 mg/100 g gallic acid equivalent. Extracts from dry plants showed higher antioxidant activities than those from fresh ones. The DPPH EC(50) values were approximately 12.15 μg/mL and 16.59 μg/mL, respectively. Antioxidant activity measured by the ABTS method yielded values higher than 718.99 μM trolox/g for dry plants, while by the Rancimat(®) system yielded protection factors exceeding 1 for all extracts, comparable to synthetic BHT. Ferulic acid was the principal phenolic compound identified and quantified through HPLC-UV in all extracts. The extracts proved effective inhibitory potential for Staphylococcus epidermidis and Staphylococcus aureus. These results showed that extracts of Euphorbia tirucalli L. have excellent antioxidant capacity and moderate antimicrobial activity. These can be attributed to the high concentration of ferulic acid.